THE ROLE OF FIXED EXPRESSIONS IN THE FORMATION OF LINGUISTICS - Bozorova Dilobar Bahodir qizi; Tillayeva Muyassar Yarbazarovna (International Engineering Journal For Research & Development, 2022)
The relevance of the topic is also due to the fact that although much work has been done on the study of language semantics, some aspects of it have not yet been sufficiently studied. These include the ability of language derivations to be reflected in dictionaries and the semantic interpretation of phraseological units. Due to the complexity of the nature of phraseological units, their meaning and semantic significance have not been fully studied in the research work so far, mainly in the study of ways of formation of phraseological units. The study examines in detail the semantic and structural features of English phraseology and how they are reflected in dictionaries. The issues raised above highlight the relevance of the topic.